CAN TRADITIONAL RETAILERS USE STRATEGY TO FIGHT AGAINST MODERN ATTACKS? - Rachmadi Agus Triono; Zuliani Dalimunthe; Helman Arif (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Despite rapid growth in online type, the majority Indonesian retail market is offline shopping because of households disperse across thousand cities and islands. However, the threat comes from corporatized modern retailers. Typically, attacks from modern retailers in the form of franchised minimarkets endangered the existence of traditional retailers which generally are small sized and independently owned by individual or household. This research investigates how traditional retailers can deliver a strategic response to the presence of modern retailers, and to examine whether there are differences in performance among business entities that use different strategic responses. We also investigate if there are differences, which strategic response would give the best result in performance. Questionnaires were distributed to 109 respondents using convenience sampling. An ANOVA was done at respective types of retailers' buyers. There is no significant evidence that the strategic response developed by traditional retailers differed from one another. Furthermore, we found that the performance of traditional retailers are below modern retailers, except for those that belong to a higher tier of performance. Higher tier traditional retailers are the best strategic group in traditional retailers and their performance statistically could equate to the performance of modern retail. Keywords: Indonesian retail market, small-scale retailer strategy, strategic group, strategic response